God's Word, Spoken or Otherwise : Sayyid Ahmad Khan's (1817-1898) Muslim Exegesis of the Bible - Ramsey, Charles M., (The History of Christian-Muslim Relations ;, 2022)
Set in British India soon after the Uprising of 1857, God's Word, Spoken and Otherwise explores the controversial and ingenious ideas of one of South Asia's most influential public thinkers, Sir Sayyid Ahmad Khan (1817-1898). Bringing to light previously unpublished material from his exegetical commentaries on the Bible and Qur'an, this study explores the interplay of natural and prophetic revelation from an intertextual perspective. The book provides fresh insight into Sir Sayyid's life and work, and underscores both the originality of his ideas, and also their continuity within a dynamic Muslim intellectual tradition.